TNFAIP2 deficiency drives formation of an immunosuppressive tumor microenvironment and confers resistance to anti-PD-1 therapy in skin cutaneous melanoma - Yaning Wang; Jinsong Wang; Zhihong Chen; Chiyang Zhong; Hao Luo; Teng Xu (Scientific Reports)
Abstract TNFα-induced protein 2 (TNFAIP2) reportedly plays a significant role in the initiation and progression of malignancy. However, its function in skin cutaneous melanoma (SKCM) is largely unknown and urgently needs to be explored. Analysis of a publicly available database revealed that TNFAIP2 was significantly downregulated in SKCM tissues vs. normal controls (P < 0.001) and that its expression was a significant indicator for SKCM diagnosis (AUC = 0.742). Patients with low TNFAIP2 expression tended to have tumors in advanced clinical stages with a poor prognosis (P < 0.01), which was validated in our cohort. Subsequent enrichment analysis revealed that genes differentially expressed between SKCM tissues with high and low TNFAIP2 expression were highly enriched in with multiple tumor immune signatures, especially immune checkpoint signalling. Immune infiltration estimation indicated that TNFAIP2 upregulation predicated increased infiltration of CD8+ T cells, B cells, NK cells, and M1 macrophages and predicted a favourable response to immune checkpoint blockade (ICB) treatment in SKCM. In the SKCM mouse model, TNFAIP2 overexpression suppressed tumor growth and lung metastasis, and this effect was even more pronounced in immunocompetent mice; notably, these mice presented increased infiltration of CD8+ T cells and M1 macrophages into the tumor microenvironment. Moreover, TNFAIP2 overexpression clearly increased the sensitivity of SKCM to anti-PD-1 immunotherapy. The above results indicate the tumor-suppressive role of TNFAIP2, which may be a promising target for improving the efficacy of ICB treatment in SKCM.